FGD On Time Management and Dual Roles of Managerial Career Women in NIP Mojokerto Area - Efendi, Imaduddin Bahtiar; Agustina, Silvi; Kusumawati, Elinda Candra; Firdaus, Ainur; Sulistiarini, Emma Budi (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2025)
This community service activity aims to explore the challenges faced by managerial level career women in managing time between work and domestic obligations. The method used was Focus Group Discussion (FGD) involving 25 female participants who served as general managers, middle managers, and HRD practitioners from domestic and multinational companies in the Ngoro Industrial Park (NIP) industrial area, Mojokerto. The discussion was directed at identifying constraints in time management, strategies for dealing with multiple roles, and formulating policy recommendations that support work-life balance. The results of the discussion showed that participants faced high mental stress due to long working hours, social expectations as wives/mothers, and lack of institutional support. These findings reinforce the results of previous studies on mental burden, role inequality, and the dominant masculine work culture. The resulting recommendations include the development of flexible work policies, equal division of labor, gender-sensitive internal mentoring, and institutional support such as counseling and childcare services. This activity is expected to encourage the development of more gender-responsive company policies and strengthen the sustainability of women's leadership roles in the industrial sector.